THE SIMULATION OF PROTOCOL 802.11 INFLUENCE ON NETWORK ACCESS METHOD FOR WIRELESS DATA COMMUNICATIONS - Suhartini, Suhartini (Jurnal Ilmiah Informatika Komputer, 2009)
This research aims to analyze the influence of traffic in relation to data transmission which arrived from severalnodes by applying 802.11 protocol with CSMA/CA method. The simulation was performed using MATLAB with 5nodes and 16 data packets with simulation time of 600 ms. The result of this experiment shows that theutilization of CSMA/CA as protocol provides better results than CSMA. Thenumber of transmitted packets improve twice as much as when using CSMA method.Keyword(s): Protocol 802.11, CSMA/CA, RTS, CTS, ACK.Subject Description : C.2. Computer-Communication Networks | C.2.0 General | Data communications